Human–Monkey Chimeras for Modeling Human Disease: Opportunities and Challenges - De Los Angeles, Alejandro (Stem Cells Dev, 2018)
The search for a better animal model to simulate human disease has been a “holy grail” of biomedical research for decades. Recent identification of different types of pluripotent stem (PS) cells and advances in chimera research might soon permit the generation of interspecies chimeras from closely related species, such as those between humans and other primates. In this study, we suggest that the creation of human–primate chimeras—specifically, the transfer of human stem cells into (non-ape) primate hosts—could not only surpass the limitations of current monkey models of neurological and psychiatric disease but would also raise important ethical considerations concerning the use of monkeys in invasive research. Questions regarding the scientific value and ethical concerns raised by the prospect of human–monkey chimeras are more urgent in light of recent advances in PS cell research and attempts to generate interspecies chimeras between humans and animals. While some jurisdictions prohibit the introduction of human PS cells into monkey preimplantation embryos, other jurisdictions may permit and even encourage such experiments. Therefore, it is useful to consider blastocyst complementation experiments more closely in light of advances that could make these chimeras possible and to consider the ethical and political issues that are raised.